Efisiensi Penggunaan Faktor-Faktor Produksi pada Usaha Tani Teh Rakyat - Nanang Yusroni (Universitas Wahid Hasyim, 2006)
The research was held on the argument that average of red union on the research area, Purbalingga Regency still under of minimize standard of the Agricultural Instance. During the last six years average of red union production on Purbalingga Regency was 12, 2 ton / ha each yield period, and it was under the minimize number, 20 – 40 ton/ ha each year period. The goal of this research were knowing how far influence of usage of production factor : the wide of area, employer, seed, fertilizer, and pesticide on production and analyzing of efficiency level for production factor usage on red union cultivation on Purbalingga Regency.The research was done at, Bojongsari district, on Purbalingga Regency. The cross section data was used and analyze instrument on the research was regression of Cobb Douglas production factor with multiple linear regression on the calculation